Nocebo-Hypothesis Cognitive Behavioral Therapy (NH-CBT) for Persons With Functional Neurological Symptoms (Motor Type): Design and Implementation of a Randomized Active-Controlled Trial - Richardson, Matt; Kleinstäuber, Maria; Wong, Dana (Frontiers in neurology, 2020)
Introduction: Functional Neurological Symptom Disorders (FNSD) are associated with high levels of disability and immense direct and indirect health costs. An innovative interdisciplinary rehabilitation approach for individuals with functional neurological symptoms of motor type–Nocebo-Hypothesis Cognitive Behavioral Therapy (NH-CBT)—combines CBT and movement retraining with video feedback embedded in a comprehensive explanatory model of the etiology of FNSD. Methods: This protocol describes the development and implementation of a phase II, parallel group, randomized controlled trial with blinded outcome assessors to compare the efficacy of NH-CBT with an active control condition (supportive counseling and movement retraining). Individuals meeting diagnostic criteria of an FNSD or psychogenic movement disorder will be randomly assigned to one of the 8-week interventions. Self-report scales of motor and other physical symptoms, symptom-related psychological variables, and assessor ratings of participants' mobility will be administered at baseline, and at 8- and 16-week follow-up. Adverse events will be monitored across all sessions and therapeutic alliance will be measured at the end of therapy. The primary statistical analysis will test the hypothesis that NH-CBT is more effective than the control intervention at the 8-week follow-up. Discussion: The therapeutic strategies of NH-CBT are theory-driven by assumptions of the predictive coding model of the etiology of FNSD. Strengths and limitations of this trial will be discussed. Trial registration : Australian New Zealand Clinical Trials Registry (ANZCTR; identifier: ACTRN12620000550909).